2022
DOI: 10.1177/11207000221082927
|View full text |Cite
|
Sign up to set email alerts
|

Dual-mobility constructs versus large femoral head bearings in primary and revision total hip arthroplasty: a systematic review and meta-analysis of comparative studies

Abstract: Background: Both dual-mobility (DM) constructs and large femoral head bearings (⩾36 mm) reduce dislocation following total hip arthroplasty (THA). There is limited research comparing DM with large bearings. Methods: A systematic review of published literature was performed including studies that compared DM with large femoral head bearings in primary or revision THA according to PRISMA guidelines. The primary outcome was revision surgery for dislocation. The secondary outcome was all-cause revision surgery. Ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Sonn et al [ 37 ], in a retrospective study of 301 revision THAs divided according to the use of DMC implants or standard cups with a femoral head of ≥40 mm, found that there were no differences in dislocation rates between the implants. Moreover, Hoskins et al [ 38 ] in a meta-analysis compared primary and revision DMC constructs versus large femoral head bearings in primary and revision THAs; they found a clear advantage for the use of DMCs in primary implants, while in THA revisions, the difference in the risk of revision surgery for dislocation was unclear. They remarked that the topic lacked a literature with medium- to long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Sonn et al [ 37 ], in a retrospective study of 301 revision THAs divided according to the use of DMC implants or standard cups with a femoral head of ≥40 mm, found that there were no differences in dislocation rates between the implants. Moreover, Hoskins et al [ 38 ] in a meta-analysis compared primary and revision DMC constructs versus large femoral head bearings in primary and revision THAs; they found a clear advantage for the use of DMCs in primary implants, while in THA revisions, the difference in the risk of revision surgery for dislocation was unclear. They remarked that the topic lacked a literature with medium- to long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…17 The improved stability and range of motion may provide a better option for younger and active patients. 18,19 Nevertheless, SNH status was associated with decreased utilization of DM indicating unequal usage to this premium technology.…”
Section: Dual Mobilitymentioning
confidence: 99%
“…The efficiency of dual mobility cups (DMC) in reducing dislocation is no longer to be proven. Since its introduction in France by Gilles Bousquet in 1974 [1], many studies have shown its efficiency in trauma, primary and revision surgeries [2][3][4][5][6][7]. These promising results were observed very soon in the original studies using first-generation DMC [8].…”
Section: Introductionmentioning
confidence: 99%